NEW GEOCHEMICAL DATA OF ISLAND-ARC ORIGIN FOR SUMATERA: THE BENGKULU CASE. - Iskandar Zulkarnain (Indonesian Institute of Sciences, 2012)
ABSTRACT Sumatera is always recognized as margin of Eurasia continental plate, where the Indian oceanic plate is considered to be subducted beneath continental materials. The subduction system has produced volcanic or magmatic rocks on Sumatera at least since Cretaceous. Chemical analytical results of volcanic rocks in Bengkulu Province on major, trace and rare earth elements reveal that the volcanic rocks are derived from two different tectonic settings where the western side showing island-arc character and the eastern side represents an active continental margin (ACM). The island-arc group is characterized by lower ratio of (Ce/P)N varying between 1.1 to 2.4 and wider range of (P/Zr)N ratio varying from 1.0 to 1.7, while the ACM group show wider variation with (Ce/P)N ratio more than 3.4 and has narrower range of (P/Zr)N ranging from 0.3 to 0.6. The REE pattern of the island-arc in spider diagram shows steady decreasing in rock/chondrite ratio from La to Lu, while the ACM type is characterized by flat trend from Eu to Lu. The results suggest that it is not the whole Sumatera showing continent character, but it is island-arc in origin from Sumatera Fault Zone to the west and becomes ACM to the east.